2016
DOI: 10.1097/meg.0000000000000507
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and risk of nonalcoholic fatty liver disease

Abstract: Hyperuricemia is associated with an increased risk of NAFLD in Asian populations. Further prospective cohort studies are needed to assess the impact of hyperuricemia on the risk of NAFLD in Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
3
16
0
4
Order By: Relevance
“…Similarly, we found that females with hyperuricemia seem to have higher NAFLD risk than males with hyperuricemia independently of age, BMI, metabolic syndrome components and other clinical variables. This result is consistent with a recent meta-analysis comprising 117,712 subjects [64]. It reported that increased NAFLD risk is markedly associated with hyperuricemia in both men (RR = 1.26, 95% CI1.15–1.37, P<0.001) and women (RR = 2.01, 95% CI1.58–2.56, P<0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, we found that females with hyperuricemia seem to have higher NAFLD risk than males with hyperuricemia independently of age, BMI, metabolic syndrome components and other clinical variables. This result is consistent with a recent meta-analysis comprising 117,712 subjects [64]. It reported that increased NAFLD risk is markedly associated with hyperuricemia in both men (RR = 1.26, 95% CI1.15–1.37, P<0.001) and women (RR = 2.01, 95% CI1.58–2.56, P<0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with these findings, our study found that serum UA and TG levels were significantly higher in T2DM patients with NAFLD, as compared with the T2DM without NAFLD. Our findings were supported by another large population study which showed that prevalence of NAFLD was elevated in participants with hyperuricemia [36]. We tentatively put forward that hepatic disease of NAFLD and hyperuricemia may play important roles in HTN and insulin resistance by influencing the associated inflammatory pathways.…”
Section: Discussionsupporting
confidence: 83%
“…A systematic review and meta-analysis by Gong et al . disclosed that hyperuricemia is associated with increased risk for nonalcoholic hepatic steatosis 28 . Studies have also shown that nonalcoholic hepatic steatosis is highly associated with metabolic syndrome, diabetes 29 , dyslipidemia, and cardiovascular disease 30, 31 .…”
Section: Discussionmentioning
confidence: 99%